Effects of different sowing dates on the phenology and accumulated heat units in three rapeseed (Brassica campestris L.) varieties - Akhter, Mst Towhida; Mannan, MA; Kundu, PB; Paul, NK (Bangladesh Journal of Botany, 2015)
A field experiment was carried out to study the effect of sowing dates on phenology and accumulated heat units of rapeseed (Brassica campestris L.). Seeds of three varieties (BARI Sarisha-14, BINA Sarisha-5 and BINA Sarisha-6) were sown on four different dates from October to December (S1-18 October, S2-2 November, S3-17 November and S4-3 December). The results indicated that the number of days required to attain different phenological stages decreased with delay in sowing. For all the phenological stages, S1 required higher heat units than that of other sowings. The plants of S1 used heat more efficiently than S2, S3 and S4. At the earlier phenological stages, phenothermal index decreased with delay in sowing, but increased at the later stages. DOI: http://dx.doi.org/10.3329/bjb.v44i1.22730 Bangladesh J. Bot. 44(1): 97-101, 2015 (March)